EDUCATORS' READINESS TO IMPLEMENT THE INDEPENDENT LEARNING CURRICULUM AT MENDUNGAN 2 ELEMENTARY SCHOOL, YOGYAKARTA - Muhammad Munir; Sabarudin; Ayu Rahayu; Farhan Ahlul Qudrani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Merdeka Belajar Curriculum is a policy of the Ministry of Education, Culture, and Research and Technology which aims to increase the effectiveness of the current curriculum. This study aims to evaluate teacher preparation in implementing Merdeka Belajar Curriculum. The research method used is a case study involving two teachers and the principal at an elementary school implementing this curriculum. Data for research is collected through interviews, observations, and documentation, then analyzed by data collection, data reduction, data presentation, and conclusion making. The research findings show that the level of teacher readiness in implementing Merdeka Belajar Curriculum in elementary schools has reached a sufficiently optimal level. However, some of the obstacles faced by teachers include a lack of understanding of the Merdeka Belajar Curriculum among both teachers and parents. In addition, the facilities and infrastructure to support this curriculum are still inadequate.